1989
DOI: 10.1101/gad.3.8.1166
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of HAP4: a third component of the CCAAT-bound HAP2/HAP3 heteromer.

Abstract: The CYCl gene of Saccharomyces cerevisiae is positively regulated by the HAP2 and HAPS proteins, which form a heteromeric complex that binds to a CCAAT box in the upstream activation site, UAS2, and which activate transcription in a nonfermentable carbon source. We carried out a genetic analysis to identify additional trans-acting regulatory factors exerting their effects through UAS2. We present the identification and characterization of a new locus, HAP4, which is shown to encode a subunit of the DNA-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
350
3

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(362 citation statements)
references
References 70 publications
9
350
3
Order By: Relevance
“…Finally, the HAP elements are also involved in regulation of HXT5 expression. Activity of the Hap2/3/4/5p complex, which probably binds to the HAP elements in the HXT5 promoter, is dependent on the Hap4p subunit, whose transcription is repressed by glucose (Brons et al, 2002;DeRisi et al, 1997;Forsburg and Guarente, 1989). Thus, the HAP elements may also contribute to HXT5 expression specifically when glucose is absent, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the HAP elements are also involved in regulation of HXT5 expression. Activity of the Hap2/3/4/5p complex, which probably binds to the HAP elements in the HXT5 promoter, is dependent on the Hap4p subunit, whose transcription is repressed by glucose (Brons et al, 2002;DeRisi et al, 1997;Forsburg and Guarente, 1989). Thus, the HAP elements may also contribute to HXT5 expression specifically when glucose is absent, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The main transcriptional regulator of this induction is thought to be the heterotrimeric transcription-activation complex HAP2/3/4. The genes for the proteins of this complex were isolated via a selection procedure that exploited the ability of the subunits of the complex to bind to UASup1 of the CYC1 gene and to activate transcription (Pinkham and Guarente 1985;Hahn et al 1988;Forsburg and Guarente 1989). Based on in vitro mobility-shift experiments, Olesen et al (1987) concluded that HAP2 and HAP3 bind to the DNA in an interdependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Based on in vitro mobility-shift experiments, Olesen et al (1987) concluded that HAP2 and HAP3 bind to the DNA in an interdependent manner. HAP4 protein does not bind DNA directly, but augments the binding of HAP2 and HAP3 (Forsburg and Guarente 1989). Mutations in any of the three HAP genes lead to a non-functional complex, with a consequently diminished induction of genes coding for mitochondrial proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cdc25-10 mutant, the glucose-responsive cAMP-activated PKA activity is downregulated, thereby increasing life span (Lin et al 2000). Hap4 is a component of the Hap complex that binds to the consensus sequences CCAAT and increases the transcription of many genes involved in mitochondrial metabolism (Forsburg and Guarente 1989). Overexpressing Hap4 has been shown to induce a metabolic shift toward respiration and extend life span (Lin et al 2002).…”
Section: A Functional Nadh Shuttle Is Required For Multiple Genetic Mmentioning
confidence: 99%